The correlation between vitamin a status and refractory Mycoplasma Pneumoniae pneumonia (RMPP) incidence in children - Yuanyuan Li; Ziyao Guo; Guangli Zhang; Xiaoyin Tian; Qinyuan Li; Dapeng Chen; Zhengxiu Luo (BMC, 2020)
Abstract Background Vitamin A plays a pivotal role in respiratory infection, accurate estimation of vitamin A status was recommended in planning and implementing interventions. As infections affect serum vitamin A productions, the real status need to be adjusted by acute phase protein (APP). Mycoplasma pneumoniae is an important cause of respiratory infection in children, the association between vitamin A concentrations and refractory Mycoplasma pneumoniae pneumonia (RMPP) remains unclear. Methods 181 MPP patients were enrolled in this retrospective study, adjusted vitamin A concentrations and other parameters were compared between RMPP and general-MPP (GMPP) patients. Multivariate logistic regression test was performed to evaluate the association between vitamin A levels and RMPP incidence, linear correlation tests were applied to evaluate correlation between vitamin A concentrations and fever duration, length of stay (LOS). Results Vitamin A concentrations in RMPP group were significantly lower than those in GMPP patients (P < 0.05), vitamin A (OR = 0.795, 95% C. I 0.669-0.946) and CRP (OR = 1.050, 95% C. I 1.014-1.087) were independently associated with RMPP incidence. Linear correlation tests found vitamin A concentrations were negatively correlated with fever duration and LOS (P < 0.001). Conclusions Serum vitamin A concentrations were independently associated with RMPP incidence, which may correlate with reduced incidence of RMPP.